Effects of supplemental tannic acid on growth performance, gut health, microbiota, and fat accumulation and optimal dosages of tannic acid in broilers - Choi, Janghan; Yadav, Sudhir; Wang, Jinquan; Lorentz, Benjamin J.; Lourenco, Jeferson M.; Callaway, Todd R.; Kim, Woo Kyun (Frontiers in Physiology, 2022)
This study was conducted to investigate the effects of different dosages of tannic acid (TA) on growth performance, nutrient digestibility, gut health, immune system, oxidative status, microbial composition, volatile fatty acids (VFA), bone mineral density, and fat digestion and accumulation in broilers and to find optimal dosages of TA for efficient growth and gut health in broilers. A total of 320 male Cobb500 broilers were randomly distributed to 4 treatments with 8 replicates including 1) tannic acid 0 (TA0): basal diet without TA; 2) tannic acid 0.5 (TA0.5): basal diet with 0.5g/kg TA; 3) tannic acid 1.5 (TA1.5); and 4) tannic acid 2.5 (TA2.5). Supplemental TA at levels greater than 972 mg/kg tended to reduce BW on D 21 (P=0.05). The TA2.5 had significantly lower apparent ileal digestibility (AID) of crude protein compared to the TA0 group. The AID of ether extract tended to be reduced by TA at levels greater than 525 mg/kg (P=0.08). The jejunal lipase activities tended to be reduced by TA at levels less than 595.3 mg/kg (P=0.09). TA linearly decreased goblet cell density in the crypts of the jejunum (P<0.05) and reduced mRNA expression of mucin 2 at levels less than 784.9mg/kg and zonula occludens 2 at levels less than 892.6mg/kg (P<0.05). The TA0.5 group had higher activities of liver superoxide dismutase compared to the TA0 group (P<0.05). Bone mineral density and contents tended to be linearly decreased by TA (P=0.05), and the ratio of lean to fat was linearly decreased (P<0.01). Total cecal VFA tended to be linearly reduced by TA at levels greater than 850.9 mg/kg (P=0.07). Supplemental TA tended to increase the relative abundance of the phylum Bacteroidetes (P=0.1) and decrease the relative abundance of the phylum Proteobacteria (P=0.1). The relative abundance of the family Rikenellaceae was the lowest at 500mg/kg TA, and the relative abundance of the family Bacillaceae was the highest at 1,045mg/kg TA. Collectively, these results indicate that the optimum level of supplemental TA would range between 500 to 900mg/kg; this range of TA supplementation would improve gut health without negatively affecting growth performance in broilers under antibiotic-free conditions.